A Review of Neuronal Pathways Associated With Consciousness. Issue 1 (February 2021) - Mulkey, Malissa; Everhart, D. Erik; Gencarelli, Amy; Sorrell, Anne; Kim, Sungham
Abstract : ABSTRACT: INTRODUCTION: Accurate communication of information regarding fluctuations in level of consciousness is critical. It is, important for nurses to understand terms related to consciousness to appropriately assess and implement plans of care. CONTENT: Although the neurobiology of consciousness is complex and multifaceted, consciousness can be conceptualized as having 2 distinct but interrelated dimensions: arousal and awareness. The different levels of consciousness are thought to fall on a continuum ranging from being fully awake to coma. CONCLUSION: This article focuses on the terms of consciousness, awareness, and arousal along with nursing implications where appropriate.